2020
DOI: 10.1186/s13065-020-00708-z
|View full text |Cite
|
Sign up to set email alerts
|

Purification, structural analysis, and stability of antioxidant peptides from purple wheat bran

Abstract: Protein derived from purple wheat bran was hydrolyzed sequentially using alcalase proteases for the production of antioxidant peptides. Purple wheat bran protein (PWBP) hydrolysates were fractionated using size-exclusion (G-25) and ion-exchange chromatography methods to identify the structure of antioxidant peptides. The free radical scavenging activity of peptides purified from PWBP hydrolysates was evaluated using superoxide anion radical-scavenging activity and determination assays of Trolox equivalent anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…SOD is the initial, critical step against oxidative stress because its activity leads to the detoxification of hydrogen peroxide (H 2 O 2 ) and superoxide radicals ( Abbasi et al 2016 ). Following this, the hydrogen peroxide dismutation reaction can be catalysed by CAT and APX into H 2 O and O 2 ( Zhang et al 2015 ; Zhao et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SOD is the initial, critical step against oxidative stress because its activity leads to the detoxification of hydrogen peroxide (H 2 O 2 ) and superoxide radicals ( Abbasi et al 2016 ). Following this, the hydrogen peroxide dismutation reaction can be catalysed by CAT and APX into H 2 O and O 2 ( Zhang et al 2015 ; Zhao et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Plant responses and adaptation mechanisms to salt stress are often separated into different categories: avoidance, sensitivity and tolerance. Avoidance is a mechanism of response to salt stress ( Zhao et al 2020 ) that allows plants to sustain fundamental physiological processes by speedy stomatal closure and a reduction in total leaf area to minimize water loss by transpiration ( Acosta-Motos et al 2017 ). Decreases in leaves may provoke a reduction in height and size of aerial parts.…”
Section: Introductionmentioning
confidence: 99%
“…However, comprehensive studies investigating PQ's antimicrobial chemicals are still scarce, and the NMR chemical identification usually required milligrams of pure compound, which is time-consuming to purify. In recent years, the advanced Orbitrap Elite Hybrid Mass Spectrometer, which combines a novel high-field orbitrap mass analyzer with a premier dual-pressure linear ion trap mass spectrometer, greatly improved MS and MS n performance and versatility, and it has become a reliable technique for a targeted and a non-targeted analysis of the chemical structure, requiring only picogram of the sample (Denisov et al, 2012;Jiang et al, 2020;Zhao et al, 2020). LC-HRMS/MS (high-resolution mass spectrometry) and MS n provide retention time, extract m/z and its fragmentation, from which the structure normally can be inferred based on comparison with standards, or published spectra of compound databases, MS/MS libraries, and molecular networking (Allen et al, 2014;Schymanski et al, 2014;Fisher et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Beyond that, antioxidant peptides can interact with metal ions in the following ways to prevent the oxidationpromoting reaction: (1) chelate metal ions and (2) as a hydrogen donor, maintain the original valence state of metal ions. 61,62 The antioxidant activity of peptides is closely related to the molecular weight, secondary structure, hydrophobicity, and amino acid residue composition and sequence. 63 Studies have shown that antioxidant peptides with a low molecular weight (<1 kDa) usually have higher activity, because they are more active in the reaction with free radicals.…”
Section: ■ Bioactive Peptides For Food Preservationmentioning
confidence: 99%
“…Besides, antioxidant peptides can reduce lipase activity, inhibiting chain reaction. Beyond that, antioxidant peptides can interact with metal ions in the following ways to prevent the oxidation-promoting reaction: (1) chelate metal ions and (2) as a hydrogen donor, maintain the original valence state of metal ions. , …”
Section: Bioactive Peptides For Food Preservationmentioning
confidence: 99%